2021
DOI: 10.5603/dk.a2021.0035
|View full text |Cite
|
Sign up to set email alerts
|

Metformin therapy and severity and mortality of SARS-CoV-2 infection: a meta-analysis

Abstract: background. It has been postulated that metformin could have anti-SARS-CoV-2 action. this raises the hypothesis that people who take metformin may have lower SARS-CoV-2 severity and/or mortality. Objectives. to conduct a meta-analysis of the association between the use of Metformin and risk of severity and mortality in SARS-CoV-2 infection. Methods. We searched PubMed, EMbASE, Google scholar, the Cochrane Database of Systematic Reviews and preprint servers (medRxiv and Research Square) for studies published be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 81 publications
(101 reference statements)
2
8
0
Order By: Relevance
“…We also used extractable raw data instead of pre-calculated ORs or HRs to determine the pooled OR for the unadjusted analysis. We found that there was a significant reduction of in-hospital mortality with outpatient or inpatient metformin therapy in patients with type 2 diabetes mellitus hospitalized for COVID-19 in the unadjusted analysis, which is in line with previous meta-analyses [39][40][41]. Furthermore, evidence obtained from observational studies is an of great importance source for clinical practice where randomized clinical trials are unavailable or infeasible [42].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We also used extractable raw data instead of pre-calculated ORs or HRs to determine the pooled OR for the unadjusted analysis. We found that there was a significant reduction of in-hospital mortality with outpatient or inpatient metformin therapy in patients with type 2 diabetes mellitus hospitalized for COVID-19 in the unadjusted analysis, which is in line with previous meta-analyses [39][40][41]. Furthermore, evidence obtained from observational studies is an of great importance source for clinical practice where randomized clinical trials are unavailable or infeasible [42].…”
Section: Discussionsupporting
confidence: 86%
“…To further compare and integrate the results of different studies and to increase statistical power, we set out to perform a meta-analysis. Prior to this meta-analysis, several meta-analyses [39][40][41] of the association between metformin therapy and severity and mortality were published, but they have issues. First, metformin therapy was not differentiated between outpatient and inpatient use, as oral hypoglycemic medications including metformin are usually held during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…We also used extractable raw data instead of pre-calculated ORs or HRs to determine the pooled OR for the unadjusted analysis. We found that there was a significant association between the reduction of in-hospital mortality and outpatient or inpatient metformin therapy for type 2 diabetes mellitus in COVID-19 patients in the unadjusted analysis, which is in line with previous meta-analyses [43][44][45]. Furthermore, evidence obtained from observational studies is an of great importance source for clinical practice where randomized clinical trials are unavailable or infeasible [46].…”
Section: Plos Onesupporting
confidence: 84%
“…Prior to this meta-analysis, several meta-analyses [43][44][45] of the association between metformin therapy and severity and mortality were published, but they have issues. First, metformin therapy was not differentiated between outpatient and inpatient use, as oral hypoglycemic medications including metformin are usually held during hospitalization.…”
Section: Plos Onementioning
confidence: 99%
“…We next compared our results with those from other publications [4][5][6][7][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. No published meta-analysis has analyzed the association between TZD or AGI and COVID-19-related mortality (Table 4).…”
Section: Comparison With Previous Meta-analysesmentioning
confidence: 99%